Analysis of Effect Service Quality and Customer Satisfaction on Customer Loyalty Burger Restaurant Bangor Medan - Ramadhan Akbari; Dewi Nurmasari Pane; Ramadhan Harahap (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2022)
This study is to analyzes the effect of service quality and customer satisfaction on consumer loyalty at Restaurant Burger Bangor Medan. The population in this study was at Restaurant Burger Bangor Medan. The number of samples in this study was 83 customers with a saturated sampling technique. The analysis technique uses multiple linear regression analysis. The results showed (1) results showed that partially the service quality variable affected customer loyalty at Burger Bangor Restaurant Medan City. (2) The results showed that partially the variable Consumer Satisfaction affected Customer Loyalty at Burger Bangor Restaurant Medan City (3).